Brain metastases of choriocarcinoma – A report on two cases - Milenković, Vera; Lazović, Biljana; Mirković, Ljiljana; Grujičić, Danica; Sparić, Radmila (Vojnosanitetski pregled, 2017)
Introduction. Gestational trophoblastic diseases (GTD) are a spectrum of tumors with a various of biological behavior and potential for metastases. It consists of hydatiform mole, invasive mole, choriocarcinoma and placental site trophoblastic tumor. Choriocarcinoma presents a very aggressive tumor with high malignant potential. Case report. We presented the two cases of choriocarcinoma with brain metastases. The first one was manifested by neurological deterioration as the first sign of metastasis, while the second patient had firstly metrorrhagia and in the further couse neurological disturbances that suggested the presence of brain tumor. In both cases we applied a combined treatment of surgery, chemotherapy and radiation therapy. Both patient survived with high quality of life. Conclusion. A successful outcome of brain metastases of choriocarcinoma was obtained by the use of a combined treatment of surgery, chemotherapy and radiation therapy. In cases of young women with brain metastases, gynecological malignancy should be always considered.
Keywords: choriocarcinoma; neoplasm metastasis; brain neoplasms; diagnosis; drug therapy; radiotherapy; neurosurgical procedures; treatment outcome